Humic substances and available nutrients influenced by tillage and weed management practices - KAVITA, KAVITA; DEVRAJ, DEVRAJ; HOODA, V S; DAHIYA, D S; KAVINDER, KAVINDER; HARENDER, HARENDER (The Indian Journal of Agricultural Sciences, 2021)
Effect of tillage and weed management practices on soil organic carbon (SOC), production of humic substancesand available N, P, K, S was studied after four years of experimentation (2016) at Agronomy Research Farm, CCSHaryana Agricultural University, Hisar, Haryana. Experiment initiated in 2012 having three tillage practices [T1:conventional tillage (CT), T2: furrow irrigated raised bed system (FIRBS) and T3: zero tillage (ZT)] and four weedmanagement practices (Two chemical weed management practices, one manual weeding practice and one weedy checkpractice). All the treatments were replicated thrice under spilt-plot design. The highest values of SOC (0.90%), Humicacid-C (0.352%), Fulvic acid -C (0.239%) and available nutrients: N (100.6 kg/ha), P (32.6 kg/ha), S (18.2 kg/ha),was observed under ZT system followed by FIRBS and CT system. However, highest available K (202 kg/ha) wasobserved under CT followed by ZT and FIRBS system. Post harvest available nutrients and SOC was significantlyhigher under weedy check treatment and at upper depth (0–5cm) under all tillage practices. Under ZT system, about10% and 24% higher SOC was observed at upper depth and about 4% and 8% higher SOC was observed at lower depththan that of FIRBS and CT systems, respectively. Conservation tillage practices (ZT and FIRBS), since contributetowards increased soil organic matter are thus able to improve soil fertility and maintain it for a longer period.